The first 90: Progress in HIV detection in Zhejiang Province, 2008-2018. - Lin Chen; Mingyu Luo; Yun Xu; Yan Xia; Xin Zhou; Wanjun Chen; Hui Wang; Tingting Jiang; Weiyong Chen; Yan Luo; Qiaoqin Ma; Jianmin Jiang; et al. (PLoS ONE, 2021)
To analyze the results of HIV screening and the HIV-positive rate based on different HIV detection strategies in Zhejiang Province, China. Data were downloaded from the AIDS Prevention and Control Information System on May 1, 2019. HIV screening, prevalence, and incidence data were analyzed from 2008 to 2018. The incidence of HIV was calculated from the results of BED testing. SPSS software (ver. 19.0) was used for the analysis. The number of people screened for HIV increased by 229.7% from 2008 to 2018, while the incidence of HIV increased from 1.14‱ (2010) to 1.67‱ (2018), peak by 2015 (2.28‱). The proportion of people screened for HIV in medical institutions increased from 62.0% in 2008 to 67.1% in 2018, while of all positive tests, 47.9% were conducted at medical institutions in 2008, which increased to 63.2% in 2018. VCT and STD clinic attendees, who had only 4.5% of all those undergoing HIV tests, accounted for 23.7% of all HIV positive in 2018. The rate of HIV-positive people and incidence of HIV both increased in Zhejiang Province between 2008 and 2015. The most effective strategy for detecting HIV new cases is screening visitors to VCT and STD clinics.